A interface currículo-educação em ciências na Amazônia: narrativa de professores em formação continuada - Silva, Simone Souza (2012)
Research on the Interface Curriculum-Education in Science and its implications for Education and Science Teaching in the Amazon from the narrative of a group of teachers in a Master Academic course from PostGraduate Program in Education and Science Teaching in Amazon of State University of Amazonas. Based on studies conducted by the authors, as Goodson (2003), Delizoicov (2004 and 2011), Cachapuz (2005), Moraes, Hachmann and Mancuso (2005), Nardi (2007), Prado and Soligo (2007), Silva (2007), Lopes (2007), Arroyo (2011), Demo (2010), and Chassot (2011. Methodology route centered on a qualitative approach narrative, supported by technical participant observation, narrative interviews, focus groups and documentary analysis. Finding that is possible being protagonist as a subject that investigates and allow yourself to be investigated for the purpose of legitimation of identity research professor from the narrative research. In addition, from analyzed, the result that was obtained from the subjects investigated, there was also evidence that the valuation of experience and expertise in continuing education of teachers in Science Education can help the process (re)think the curriculum in the Amazon